已知ab^2=-6,求-ab(a^2b^5-ab^3-b)的值
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 22:38:44
已知ab^2=-6,求-ab(a^2b^5-ab^3-b)的值已知ab^2=-6,求-ab(a^2b^5-ab^3-b)的值已知ab^2=-6,求-ab(a^2b^5-ab^3-b)的值ab^2=-6
已知ab^2=-6,求-ab(a^2b^5-ab^3-b)的值
已知ab^2=-6,求-ab(a^2b^5-ab^3-b)的值
已知ab^2=-6,求-ab(a^2b^5-ab^3-b)的值
ab^2=-6
所以-ab(a^2*b^5-ab^3-b)
=-a^3b^6+a^2b^4+ab^2
=-(ab^2)^3+(ab^2)^2+(ab^2)
=-(-6)^3+(-6)^2+(-6)
=216+36-6
=246
-ab(a^2b^5-ab^3-b)
=-a^3b^6+a^2b^4+ab^2
=-(ab^2)^3+(ab^2)^2+ab^2
=-(-6)^3+(-6)^2+(-6)
=216+36-6
=246
已知ab^2=6,求ab(a^2b^5-ab^3-b)的值
已知ab^2=-6,求-ab(a^2b^5-ab^3-b)的值
已知ab^2=6,求ab(a^2b^5-ab^3-b)的值
已知ab^2=6,求ab(ab^3+a^2b^5-b)
已知ab^2=-6求-ab(a^2b^5-ab^3-b)
已知ab²=6,求ab(a^2b^5-ab^3-b)的值
已知a^2b^3=6,求(ab^2)^2*(ab)^3*ab^2
已知a+b=3,ab=2 求 ab+2ab+ab 的值
已知a-b=,ab=1/8,求-2ab+ab+ab的值
已知a+b=6,ab=5,求a^2b+ab^2的值.
已知b-a=6,ab=7,求a^2b-ab^2的值
已知a+b=7,ab=6,求a^2b+ab^2的值
已知a+b=-5,ab=6,求a^2b+ab^2
已知a/b=-2,求a²-2ab/6ab-7b²
已知a/b=-2,求(a²-2ab)/(6ab-7b²)
已知:a-b=4,ab=3,求多项式(2a+5b-3ab)-(a+6b-ab)-(2ab+2b-2a)的值
已知a+b=-5,ab=6,求2(ab-3a)-3(2b-ab)
已知(a+b)的平方+|2b-1|=0,求6ab-2ab-3(ab-a)